Hegemonic Practices in Hussein Al-Wad’s Sa’ãdatuhu As-Sayyidul Wazĩr Novel - Rizqi Handayani; Ahmad Syafa’at Junaid (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2022)
PurposeThis article aimed to describe the hegemonic efforts made by the ruling regime in strengthening its power, as recorded in the novel Sa'ãdatuhu As-Sayyidul Wazĩr. This article also revealed the social problems that occurred in Tunisia as a result of the application of the hegemony that was exercised during the regime of Zine El Abidine Ben Ali. MethodThis qualitative study used a library research design that relied on the novel Hussein El-Wad’s Sa’ãdatuhu As-Sayyidul Wazĩr as the primary data source, while the secondary data sources were various literature in the form of books, articles, websites and other information related to the research topic. Results/FindingsThe study revealed the problem of hegemonic practices carried out by authoritarian regimes for decades, both in civil society and political society. The long-standing authoritarian rule had resulted in the country to cope with various problems, such as rampant corruption, increasing unemployment rates, and the deprivation of civil rights of Tunisian citizens. ConclusionThe practice of hegemony as a power strategy carried out by the ruling regime, Zainal Abidin bin Ali, did not work well, as a result various social problems emerged which resulted in the collapse of power and public trust in his government.